Outcome measures of palliative care programs and interventions implemented in nursing homes: a scoping review protocol. Issue 2 (25th February 2022) - Meng, Lingyuan; Peters, Micah D.J.; Sharplin, Greg; Eckert, Marion
ABSTRACT: Objective: This scoping review aims to identify and map the outcomes reported from evaluations that measure the effectiveness and acceptability of palliative care programs and interventions in residential aged care facilities. Introduction: As the population ages, there is increasing attention on implementing new interventions and programs to improve palliative care in residential aged care facilities. However, there is no standard evaluation for intervention implementation. Mapping the outcome measures used in evaluations of diverse palliative care interventions in residential aged care facilities has not been explored recently. Inclusion criteria: This review will consider studies involving older adults (aged 50 years and above) in any country living and receiving care in residential aged care facilities. This review will exclude literature that focuses on other age groups, and people receiving palliative care in other care settings, such as hospitals, palliative care inpatient units, sheltered housing, cancer centers, own homes, and hospices. Methods: This scoping review will follow the JBI methodology for scoping reviews. This scoping review will identify both published and unpublished (eg, gray literature) primary studies, as well as reviews. The databases to be searched for published studies will include MEDLINE, Emcare, ProQuest, Embase, PsycINFO, Web of Science, Scopus, and the Cochrane Library. The search will be limited to evidence published in English from 2008 to the present. Visual, tabular, and accompanying narrative summaries will be used to present the results.